Model for Calculating Cost of Laundry Services by Considering Environmental Impacts and Costs - Elsje Kosasih; Atty Yuniawati; Verawati Suryaputra; Amelia Limijaya (Universitas Muhammadiyah Yogyakarta, Indonesia, 2019)
This research aims at developing a model for calculating cost of laundry services performed by small-scale laundry businesses which incorporates environmental impact and costs into the model. The activity-based costing method is used to assign indirect costs to the cost object. This research is a continuation of the previous research conducted by the authors. Since environmental impacts and costs are considered, there will be changes in the resources and activity consumed, compared to the original model. The authors identified several environmental costs, such as eco-detergent and plastic, government fines, loss of customers and environmental costs borne by wider society. In analyzing the environmental costs, EPA classification is used. The suggested model is still in the theoretical phase, as some environmental costs arising from laundry business activities are difficult to measure. Some recommendations to laundry businesses and government are provided.